Analisis Faktor Penghambat Pengembangan Usaha Kopi Kenanga terhadap UMKM di Desa Lubuk Garam Tahun 2023 - Muhammad Dhafa Amardi; Lucky Marcelino; Rendi Christoper; Septia Laisya Ananda; Winda Hardila Fitri; Indri Anggareini; Yovani Agustina Silaban; Caroline Losawene; Faradina Faradina (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Economic activity is important in keeping the country's economy running well. One of these economic activities is the production process in which individual or group activities in managing raw materials into goods are carried out in order to increase the use value of the goods. Economic activities, especially production, can run well if the constraining variables can be overcome well. In this paper, the author analyzes what factors inhibit the development of the Kenanga Coffee business located in Lubuk Garam village, Siak Kecil Regency, Bengkalis Regency, Riau Province by direct observation in the field and interviews with related parties.